The Paris wife [large type] : a novel - McLain, Paula (Center Point Pub., 2011)
In Chicago in 1920, 28-year-old Hadley Richardson meets Ernest Hemingway. Following a whirlwind courtship and wedding, the pair set sail for Paris and become the golden couple in a lively group of expatriots, including Scott and Zelda Fitzgerald, Gertrude Stein, Ezra Pound, and Gerald and Sara Murphy. But as Hadley struggles with self-doubt and jealousy, Ernest wrestles with his burgeoning writing career and both must confront a deception that could prove the undoing of one of the greatest romances in history.